Cognitive component of Tolerance in Pedagogic Education - O. V. Akimova (Obrazovanie i Nauka, 2015)
The paper looks at one of the urgent educational problems of tolerance development by teachers and students; tolerance being viewed as the openness to the new knowledge acquisition, willingness to understand other people and cooperate with them, and therefore the opportunity for self- development.The paper outlines the ways of tolerant attitudes formation by all the human subjects of educational process; the concept of person oriented teaching is considered to be the basic one for tolerance development. To optimize the specialists’ training for communication at any level of professional environment, the cognitive activity educational model is suggested, providing the ways out of any complicated pedagogical situation. The cognitive psychology concepts give the background for the above model. The education in question promotes the intellectual level of the prospective teachers, intensifies their creative potential, methodological thinking and practical experience, as well as tolerance development in professional communication process.